Are artificial burrows efficient conservation tools for seabirds? A case study of two sympatric shearwaters on neighbouring islands and guidelines for improvement. (November 2015) - Bourgeois, Karen; Dromzée, Sylvain; Vidal, Eric
Abstract: Seabirds are one of the most threatened animal taxa worldwide as they have to deal with threats both at sea and on their breeding grounds. One of these threats is the loss and deterioration of their nesting habitat. Here, we evaluated the long-term effectiveness of providing artificial burrows for the conservation of Yelkouan ( Puffinus yelkouan ) and Scopoli's ( Calonectris diomedea ) shearwaters on two islands of the Hyères archipelago (Mediterranean, France). We estimated and compared the longevity, occupancy of and breeding success in artificial burrows and natural cavities. We also analysed factors affecting these three parameters in artificial burrows to optimize their installation for the conservation of our study species. Although their efficacy depended on the species and the island considered, artificial burrows provided more stable and persistent breeding habitat (12-years persistence: 80% vs. 72%), allowed the recruitment of new breeders and good reproductive success (49–76%), and probably reduced inter-specific competition for nesting cavities, across the two islands. The characteristics of both artificial burrows and the areas where they were installed affected artificial burrow efficacy in terms of longevity and occupancy by shearwaters. Thus, artificial burrows were successful tools for the conservation of these two Mediterranean species of shearwaters, particularly when their design and installation were optimized by limiting the risk of their destruction and by selecting burrow and habitat characteristics that enhance their occupancy by the target species. The evaluation of such conservation measures should be performed for every species and site to help managers design and implement effective conservation plans. Highlights: We assessed artificial burrow efficacy for Yelkouan and Scopoli's shearwaters. Efficacy depended on the species and the island considered. Artificial burrows provided more stable and persistent breeding habitat. They allowed the recruitment of new breeders and good breeding success. Their benefits can be maximized by optimizing their design and installation.